Declining business dynamism in Europe: The role of shocks, market power, and technology - Filippo Biondi; Sergio Inferrera; Matthias Mertens; Javier Miranda (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
We study the changing patterns of business dynamism in Europe after 2000 using novel micro-aggregated data that we collect for 19 European countries. In all of them, we document a decline in job reallocation rates that concerns most economic sectors. This is mainly driven by dynamics within sectors, size classes, and age classes rather than by compositional changes. Large and mature firms show the strongest decline in job reallocation rates. Simultaneously, the shares of employment and sales of young firms decline. Consistent with US evidence, firms' employment changes have become less responsive to productivity. However, the dispersion of firms' productivity shocks has decreased too. To enhance our understanding of these patterns, we derive a firm-level framework that relates changes in firms' productivity, market power, and technology to job reallocation and firms' responsiveness.
Keywords: D24; J21; J23; J42; L11; L25; 330; Business dynamism; productivity; responsiveness of labor demand; market power; European cross-country data